The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1063/1.5003524
|View full text |Cite
|
Sign up to set email alerts
|

A review on the effect of fly ash characteristics and their variations on the synthesis of fly ash based geopolymer

Abstract: Abstract. There are more than four decades since the last 1970s where geopolymers concrete was first introduced and developed to use as a replacement to conventional concrete material which uses cement as a binder. And since the last two decades, geopolymers which utilized fly ash as aluminosilicate source material, i.e. fly ash based geopolymers, have been investigated. Many researchers present how to produce the best fly ash based geopolymer with a various source of constituent material as well as mixing for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 30 publications
1
33
2
1
Order By: Relevance
“…It means that silica tetrahedral units become available for the polycondensation reactions. SiO4and AlO4units are able to form a new network where the negative charge of IV-fold coordinated Al 3+ is balanced by the positive charges of Na + ions from the alkaline solution [47,11]. The reaction process leads to the formation of a geopolymer gel that acts as the matrix phase, which bind unreacted particles, forming a composite geopolymer material.…”
Section: Discussionmentioning
confidence: 99%
“…It means that silica tetrahedral units become available for the polycondensation reactions. SiO4and AlO4units are able to form a new network where the negative charge of IV-fold coordinated Al 3+ is balanced by the positive charges of Na + ions from the alkaline solution [47,11]. The reaction process leads to the formation of a geopolymer gel that acts as the matrix phase, which bind unreacted particles, forming a composite geopolymer material.…”
Section: Discussionmentioning
confidence: 99%
“…Fly ash, either with low calcium (class F) or high calcium (class C) content, is a material rich in silica and alumina, and can be used as a precursor in making geopolymer. The activation of the source material occurs in the presence of a highly alkaline solution, commonly a combination of sodium hydroxide and sodium silicate (Wattimena et al 2017;Yildirim et al 2011). The ratio and content of the two alkalis determine the characteristics of the geopolymer concrete (Arioz et al 2012;Hardjito et al 2004;Mustafa et al 2011;Rangan 2010;Rattanasak and Chindaprasirt 2009;Thunuguntla and Gunneswara Rao 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was necessary to make reasonable use to eliminate solid waste. Research suggested that FA with large specific surface area and porosity can be used to adsorb PCM; besides, FA is also a commonly used concrete mineral admixture; thus, it is feasible to use FA as a carrier to adsorb Na 2 SO 4 ·10H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was necessary to make reasonable use to eliminate solid waste. Research suggested that FA with large specific surface area and porosity can be used to adsorb PCM; besides, FA is also a commonly used concrete mineral admixture 27,28 ; thus, it is feasible to use FA as a carrier to adsorb Na 2 SO 4 ·10H 2 O. Therefore, in this paper, porous solid waste FA was chosen as an adsorption carrier of Na 2 SO 4 ·10H 2 O to form the Na 2 SO 4 ·10H 2 O/FA composite PCM (FAPCM).…”
Section: Introductionmentioning
confidence: 99%